Effect of shear and tensile-dominant cyclic loading on failure in SnAgCu solder. (May 2021) - Kuczynska, M.; Maniar, Y.; Becker, U.; Weihe, S.
Abstract: In the first part of this paper the differences between simulated SN-Curves under shearing and tensile cyclic loads are presented and compared with measurements published by A. Deshpande and A. Dasgupta [1, 2]. The measurements under the two load modes are simulated until a significant force reduction. The material model used in this work is based on visco-plasticity extended with an implicit damage formulation, enabling damage-driven cyclic softening of the structure. Additionally, multiaxiality of governing stress state is intrinsically included, with aim to account for different damage evolutions under shear and tensile load cases. The calculated damage paths are investigated and compared with cross-sections. Finally, numerically determined times to failure under different shear and tensile load levels are represented by means of SN-Woehler curves, showing a good agreement with experimental findings. Second part of the paper extends the investigation scope to lifetime prediction of a chip resistor soldered to free expanding PCB subjected to temperature cycling with variation of temperature amplitude, mean temperature and dwell time duration. The component is simulated under different temperature profiles until a specific lifetime reduction is observed. Also in this case, simulated lifetime is compared with measured data, and a good agreement with experimental results is achieved. Highlights: The paper presents load-mode dependent absolute lifetime prediction of solder joints in FE simulation. Coupled visco-plasticity damage formulation is used in this work. Predictions are validated on example of isothermal mechanically induced cyclic load test under shear and tensile dominant load, as well as thermomechanical cycling load of soldered chip resistor. Presented modelling approach allows prediction of failure time and locus with high accuracy.